Pengaruh Simulasi Surgical Safety Checklist Digital Terhadap Implementasi Surgical Safety Checklist di Instalasi Bedah Sentral - Setyoraharjo, Tuhu; Saputro, Dwi Nugroho Heri (Jurnal Kesehatan, 2024)
The use of the surgical safety checklist (SSC) at the Central Surgical Installation of Ngesti Waluyo Parakan Christian Hospital still reaches 80%. At times of tight operating schedules, using conventional SSC forms requires more time. This causes the surgical team to have difficulty adhering to the SSC procedure’s correct timing. The purpose of this study is to determine the effect of simulated use of digital SSC on the implementation of SSC. This study used a pre-experimental design with a one-group pretest and posttest approach on 12 saturated sampling respondents, and the data was analyzed using the Wilcoxon Test. The results of the intervention with the use of digital SSC showed an increase from a pretest value of 21.0000 to a posttest score of 23.9167, or about 12.15%. The results of the Wilcoxon Test showed a ρ-value of 0.002 (< α= 0.05), which showed that there was an influence of the simulation of the use of digital SSC on the implementation of SSC at the Central Surgical Installation of Ngesti Waluyo Parakan Christian Hospital.